Yields of projectile fragments in sulphur-emulsion interactions at 3.7 A GeV. (May 2017) - Kamel, S.; Osman, W.; Fayed, M.
Abstract: This work presents the basic characteristics of singly, doubly and heavily charged projectile fragments (PFs) emitted in inelastic interactions of 32 S ions with photo-emulsion nuclei at Dubna energy (3.7 A GeV). Our experimental data are compared with the corresponding data for other projectiles at the same incident energy. The study of mean multiplicities of different charged PFs against the projectile mass shows a power-law relationship. The multiplicity distributions of singly and doubly charged PFs have been fitted well with a Gaussian distribution function. The yields of PFs broken up from the interactions of 32 S projectile nuclei with different target nuclei are studied. The beam energy dependence in terms of the various order moments is studied as well.